Pesantren di Tengah Arus Modernitas: Strategi Pemeliharaan Warisan Islam di Indonesia - Bahij, Muhammad Alfan; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2024)
Pesantren in Indonesia faces two main challenges: finding a balance between Islamic tradition and modern education and training scholars who can adapt to modern knowledge. This article provides insights into the historical role of pesantren, challenges of modernity, and problem-solving strategies. Pesantren responds to challenges by accelerating the learning of religious materials, focusing on language skills improvement, developing learning materials, modernizing education, integrating traditional and modern elements, and preserving traditional values. The research aims to analyze the historical role of pesantren, assess modernity challenges, identify pesantren strategies, and evaluate sustainability and adaptability. The research design includes a case study involving various pesantren across Indonesia. Thus, this study is expected to offer a deeper understanding of how pesantren preserves and develops Islamic heritage amid the currents of modernity.